2022
DOI: 10.1002/wrna.1723
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA in disease: Basic properties and biomedical relevance

Abstract: Circular RNAs (circRNAs) represent a class of covalently closed RNA molecules with great diversity in molecular features, functions, and regulatory mechanisms. Emerging advances in our understanding of circRNA biogenesis, nuclear export, and stability control have been made very recently. In particular, novel roles of circRNAs in diverse human diseases are increasingly recognized. Various circRNAs have been found to affect many disease-relevant pathways through a diverse array of mechanisms, including forming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 138 publications
0
15
0
Order By: Relevance
“…The latest achievements in molecular biology allow us to assess the role of exosomal circRNAs in cancer resistance to cisplatin treatment. This form of nucleic acid is primarily responsible for controlling parental gene expression through various mechanisms, including miR sponges [ 85 ], which is particularly important in understanding the role of exosomal circRNAs in cancer cells acquiring cisplatin resistance. As with lncRNA, circRNA disrupts the miR-mRNA axis by decreasing miR and consequently increasing the mRNA expression of several oncogenes, leading to the acquisition of resistance to cisplatin.…”
Section: Exosomes As Chemoresistance Mediatorsmentioning
confidence: 99%
“…The latest achievements in molecular biology allow us to assess the role of exosomal circRNAs in cancer resistance to cisplatin treatment. This form of nucleic acid is primarily responsible for controlling parental gene expression through various mechanisms, including miR sponges [ 85 ], which is particularly important in understanding the role of exosomal circRNAs in cancer cells acquiring cisplatin resistance. As with lncRNA, circRNA disrupts the miR-mRNA axis by decreasing miR and consequently increasing the mRNA expression of several oncogenes, leading to the acquisition of resistance to cisplatin.…”
Section: Exosomes As Chemoresistance Mediatorsmentioning
confidence: 99%
“…Approximately 20% of mammalian genes express circRNAs, and while these ncRNAs are present in various organs, their enriched expression in the brain makes them an appealing target for the treatment of neuropsychiatric disorders ( 117 , 118 ). circRNAs play important roles as transcriptional, post-transcriptional, and/or translational regulators through various mechanisms, most notably as a sponge for miRs ( 119 ). Compared to linear RNAs, circRNAs are highly stable ( 120 ), and thus may also mediate long-term effects in several disease states.…”
Section: Introductionmentioning
confidence: 99%
“…9 With covalently closed structures, circRNAs express specifically and stably in eukaryotes, acting as miRNA sponges, transcriptional factors, translational templates, binding RNAs, or scaffolding of proteins to affect cell behavior. [10][11][12] Recent studies have indicated that circRNAs express abnormally in PAH patients and animal models, contributing to the development and progression of PAH. 13 It has been found that certain cirRNAs, 14 including hsa_-circ_0002062, hsa_circ_0022342, hsa_circ_0016070, and circ-calm4 dysregulated in PAH patients or/and experimental PAH models, show proproliferation effects on PASMCs and association with the vascular remodeling in PAH.…”
Section: Introductionmentioning
confidence: 99%